Gut-directed hypnosis and hypnotherapy for irritable bowel syndrome: a mini-review - Häuser, Winfried (Frontiers in Psychology, 2024)
Irritable bowel syndrome (IBS) is a frequent health condition which can be associated with functional disability and reduced health-related quality of life. IBS is classified as a disorder of the brain-gut axis. IBS is a very heterogenous condition with regards to the underlying pathophysiological mechanisms, the clinical picture and the amount of functional impairment. Within a biopsychosocial model of IBS psychosocial factors can play a role in the in the predisposition, triggering and development of chronicity. Somatic or psychosocial or a mixture of both factors might predominate in an individual patient. Gut-directed hypnosis is a special type of medical hypnosis combining standardised gut-directed suggestions (hypnosis) with suggestions tailored to the psychological characteristics of the patient (hypnotherapy). Of brain-gut behavioral therapies, cognitive bahvioral-based interventions and gut-directed hypnosis have the largest evidence for both short-term and long-term efficacy in controlled trials for IBS and are recommended by current European and North American gastroenterology guidelines as second line treatment options. Standardised gut-directed hypnosis is available by audiotapes and can be part of a multicomponent self-management approach by digital health applications. It can be used – based on the patient‘s preferences—as first line therapy for mild forms of IBS. Severe forms of IBS require face-to-face interdisciplinary management. Standardised gut-directed hypnosis and hypnotherapy tailored to the individual patient can be part of this approach.